2014
DOI: 10.1128/jcm.01578-14
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae from Urine Samples by Use of the ESBL NDP Test

Abstract: From June to September 2012, 500 urine samples were recovered from patients with urinary tract infections (UTI) due to Gramnegative bacilli (>10 4 leukocytes/ml and >10 5 Gram-negative isolates/ml) who visited the University hospital Bicêtre (France). They were challenged with extended-spectrum-␤-lactamase (ESBL)-producing Enterobacteriaceae (ESBL-E) using the rapid diagnostic ESBL NDP test. Results of the ESBL NDP test were compared to the results of the double-disc susceptibility test (DDST) performed on sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
2
24
1
1
Order By: Relevance
“…We believe that this is a major shortcoming in a comparison with the Rapid ESBL NDP test, since such a control allows a better appreciation of the color change (especially for weak-positive strains) and allows the detection of possible falsepositive results due to nonspecific reactions (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this is a major shortcoming in a comparison with the Rapid ESBL NDP test, since such a control allows a better appreciation of the color change (especially for weak-positive strains) and allows the detection of possible falsepositive results due to nonspecific reactions (11).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it requires an additional delay (2 h versus 20 min) for reading the results that may be considered significant for patient management and antibiotic stewardship. Finally, we believe that the use of rapid biochemical tests for detecting ESBL producers from clinical sites (11,14) will be an alternative to molecular techniques, since they are easy to implement, affordable, and may detect any kind of ESBL.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, conventional PCR was used to screen for the presence of bla PER and bla GES (12). We performed phenotypic tests for carbapenemase production using the Carba NP test and a combined-disk method (CDM) using imipenem and cloxacillin in isolates that tested negative for the presence of carbapenemase genes (13,14). The sequencing of PCR products was performed in order to confirm the identities of the detected genes.…”
mentioning
confidence: 99%
“…Although these methods are rapid and simple and allow direct assessment of clinical samples (Dortet et al, 2014a(Dortet et al, , 2014bGallah et al, 2014), their visual interpretation may give rise to ambiguity across different microbiology laboratories (Maurer et al, 2015;Simner et al, 2014;Tijet et al, 2013). Simner et al (2014) reported that the degree of color change used to determine positive results varied, while Tijet et al (2013) reported that intermediate color changes caused discrepancies between the interpretations of the findings made by 2 different laboratories.…”
Section: Discussionmentioning
confidence: 96%